Host community college education: Perceptions of teachers and students on Rohingya influx in Cox’s Bazar in Bangladesh - Roy, Sodip; Behera, Santosh Kumar (Journal of Interdisciplinary Studies in Education, 2025)
This study highlighted how teachers and students perceive the effects of the influx of Rohingya refugees on the teaching-learning environment of colleges for higher education in Cox’s Bazar district of Bangladesh. It revealed the issues of admission, the academic environment of the colleges, the attendance and performance of the students, pedagogical changes, the learning attitudes of the students, and the retention, graduation, and well-being of the prime stakeholders. To that end, it deployed an interpretivist approach and qualitative methods of in-depth interviews and focus group discussions with teachers and students from the targeted colleges of the district. In thematic analysis, both teachers and students perceive the crisis negatively, which they have identified as a ‘generation gap’ in terms of contributions to the nation's human resources. The teaching-learning environment of college education has deteriorated since the influx and crisis that has occurred in the locality. Some ad hoc pedagogical-cognitive and local decisions have been made to continue education minimally.